Modifying the phenyl group of PUGNAc: reactivity tuning to deliver selective inhibitors for N-acetyl-d-glucosaminidases12. Issue 12 (29th February 2016) - Hattie, Mitchell; Cekic, Nevena; Debowski, Aleksandra W.; Vocadlo, David J.; Stubbs, Keith A.
Abstract : The synthesis of analogues of the potent N -acetylhexosamindase inhibitor PUGNAc are described and were found to vary in both potency and selectivity against a set of biologically important N -acetyl-d -glucosaminidases. Abstract : The synthesis of analogues of the potent N -acetylhexosaminidase inhibitor, PUGNAc, are described. These compounds were assayed against a set of biologically important N -acetyl-d -glucosaminidases and were found to vary in both potency and selectivity.